"Operation Bwezani": The Army, Political Change, and Dr. Banda's Hegemony in Malawi (Nordic Journal of African Studies, 2004)
When the Malawi Army violently disarmed the Malawi Young Pioneers (MYP), a paramilitary wing of the Malawi Congress Party (MCP), in Operation Bwezani at the height of the political transition in December 1993, their action was hailed as marking a turning point in Malawi Army relationship to politics. It was also cheered as a profoundly significant catalyst for the political transition to democracy from Banda's autocracy. This article, however, argues that the fact that for close to thirty years the army did not act against Banda or his repressive machinery even when the army itself was a victim indicates the extent of Banda's hegemony in Malawi. Banda's hegemony undermined the Army's potential for resistance to oppression in Malawi. It concludes that the Army's action to disarm MYP was the result of the civilian political transition and not necessarily the cause. The, Army, therefore, was more of a beneficiary of the political transition than a catalyst.